Matrix and Inverse Matrix Projective Synchronization of Chaotic and Hyperchaotic Systems with Uncertainties and External Disturbances - Shukla, Vijay K.; Mishra, Prashant K.; Srivastava, Mayank; Singh, Purushottam; Vishal, Kumar (Discontinuity, Nonlinearity, and Complexity, 2026)
This paper investigates matrix and inverse matrix projective synchronization of chaotic and hyperchaotic systems with uncertainties and external disturbances. The sufficient conditions for achieving matrix projective synchronization (MPS) and inverse matrix projective synchronization (IMPS) of two chaotic and hyperchaotic systems are obtained. Two controllers, one for MPS and other for IMPS are designed for synchronization and based on the design, the synchronization of considered chaotic and hyperchaotic systems is achieved using these controllers. Lyapunov stability theory is used to study the problem and numerical simulations are introduced to exhibit the adequacy of the MPS and IMPS.